Painéis de sinalização dos níveis do óleo dos mancais de escora e mancais guia da turbina das unidades geradoras da Casa de Força II da UHE – Tucuruí - TRINDADE, Fagner Baia (2018)
This paper presents the implementation, the turbine shaft, a signaling panel oil level in tanks Bearing anchor and guide bearing turbine, generating units of the Powerhouse II. This project aims to eliminate the difficulty operators of the Tucuruí Hydroelectric Plant face when they need to perform the reading of the oil level in the turbine well as on site there is a reliable signaling and easy access that can provide this information. Sometimes it is necessary to use a ladder to perform the reading of the thrust bearing oil level in order to prevent parallax error. This situation creates the operator to the risk of falling and thus physical injuries. The lower bowl of the oil level display bearing guide is in place of difficult access, being necessary to remove the turbine pit grid and into confined spaces. The signaling panel will be connected to the terminals of level switches that monitor the oil level in the tank bearing. It will consist of LEDs (Light Emitting Diodes) to inform in real time, reliably and safely, the oil level Bearing anchor and bearings of the turbine guide. It will be installed in Table Terminal turbine, located in the access to the well of the turbine.